Exploring the relationships between sexual violence, mental health and perpetrator identity: a cross-sectional Australian primary care study - Laura Tarzia; Sharmala Thuraisingam; Kitty Novy; Jodie Valpied; Rebecca Quake; Kelsey Hegarty (BMC, 2018)
Abstract Background Research supports the association between adult sexual violence (SV) and poor mental health. However, most studies focus on rape and physical sexual assault. Little is known about how more subtle forms of SV affect women's well-being. Furthermore, evidence for the impact of the perpetrator's identity is mixed. There is also little data from clinical populations to help health practitioners identify SV. This paper addresses these gaps by exploring the associations between different types of adult SV, perpetrator identity, and women's mental health in the Australian primary care setting. Methods We conducted a descriptive, cross-sectional study in general practice clinics. Adult women completed an anonymous survey while waiting for the doctor. Measures included PHQ-9 (depression), GAD-7 (anxiety) and PCL-C (post-traumatic stress disorder). SV was measured using items from the National Intimate Partner and Sexual Violence Survey and categorised into three groups (rape/sexual assault; coercive behaviours and/or reproductive control; and unwanted sexual contact). Results We found significant associations between rape/sexual assault and poor mental health, and between coercion and/or reproductive control and higher PTSD and anxiety scores, compared to women with no SV experiences. SV perpetrated by an intimate partner was associated with significantly higher mean PTSD scores than SV perpetrated by a stranger, and significantly higher depression scores than SV perpetrated by another known person. Conclusion Findings suggest that associations between SV and mental health are mediated by type of SV and perpetrator identity. Health practitioners should enquire about different types of SV beyond stranger rape as a cause of poor mental health, and about perpetrator identity to inform them about the likelihood of ongoing symptoms.